The Impact of Neighborhood Disadvantage on Asthma Prevalence in a Predominantly African-American, Chicago-Based Cohort. Issue 4 (24th January 2023) - Luo, Jiajun; Kibriya, Muhammad G; Shah, Sameep; Craver, Andrew; De La Cruz, Sebastian; King, Jaime; Olopade, Christopher O; Kim, Karen; Ahsan, Habibul; Pinto, Jayant; Aschebrook-Kilfoy, Briseis
Abstract: This study aimed to investigate the joint effect of neighborhood disadvantages on asthma prevalence and evaluate whether individual-level variables protect residents against neighborhood disadvantages. Data from the Chicago Multiethnic Prevention and Surveillance Study (from 2013–2020) were analyzed. Eight neighborhood characteristics were measured using the Chicago Health Atlas, including neighborhood unsafety, limited access to healthy food, neighborhood alienation, severe rent burden, vacant housing, single-parent household, neighborhood poverty, and unemployment. A structured questionnaire measured asthma diagnosis (childhood or adulthood) and individual-level variables including sex, age, income, education, and race. Weighted quantile sum (WQS) regression was used to evaluate the impact of neighborhood disadvantages. Stratified analysis was performed by income and education. A total of 6, 592 participants (mean age = 53.5 (standard deviation, 11.1) years) were included. Most of the study population were non-Hispanic Black (82.5%) and reported an annual household income less than 15, 000 (53%). Asthma prevalence was 23.6%. The WQS index, which represents the overall neighborhood disadvantages, was associated with asthma prevalence (odds ratio = 1.14, 95% confidence interval: 1.07, 1.22) when adjusted for individual-level confounders. Neighborhood poverty contributed 40.8% to the overall impact, followed by vacant housing (23.1%) and neighborhood alienation (22.9%). When stratified by individual-level income or education, no difference was observed for the association between WQS index and asthma prevalence.